An evaluation of explicit pseudo-steady-state approximation schemes for stiff ODE systems from chemical kinetics - Verwer, Jan; Loon, M. van (1993)
Abstract: "This note discusses a pseudo-steady-state approximation approach for solving chemical kinetics equations in reactive flows. For a set of three example problems from atmospheric chemistry a comparison is presented between an explicit pseudo-steady-state solver and the two implicit state-of-the-art solvers RADAU5 and DASSL from the numerical stiff ODE field."
Keywords: Chemical kinetics